Factors affecting the professional performance of teachers (An analytical social study) - دندش أمل; دارين حسن (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
In light of the challenges faced by the people of our Syrian society from war, earthquakes and others – especially teachers as the subject of our research, this study came to identify the most important factors affecting the professional performance of teachers And how it contributes to raising the efficiency of their ability level in educational institutions, through studying the teacher’s job performance based on special standards that administrations rely on to evaluate teachers – it was necessary to identify the professional performance of teachers in the first place, and the extent of the influence of factors in improving this performance, and to identify the most prominent of these. Factors, and identifying the difficulties that teachers face in our society.